APPLIED PROBLEMS OF PROVISION OF CONSTITUTIONAL RIGHTS OF CITIZENS IN THE PROCESS OF ADAPTATION OF THE LEGISLATION OF UKRAINE TO ACQUIS COMMUNAUTAIRE OF THE EUROPEAN UNION - Бєлкін, Леонід Михайлович; Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: on specific examples of Ukrainian lawmaking the danger of violation of the constitutional rights of citizens in the process of formal implementation of the «European» norms is investigated. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: on concrete examples of recent lawmaking, practical dangers for the rights of citizens of the formal implementation of «European» norms in the legislation of Ukraine are shown. Discussion: this «adaptation» discredits the European choice of Ukraine and the adaptation of Ukrainian legislation to the acquis communautaire of the EU. The article examines the dangers of violation of the constitutional rights of citizens in the process of the formal implementation of the «European» norms with concrete examples of Ukrainian lawmaking. With concrete examples of recent lawmaking, practical dangers for the rights of citizens of the formal implementation of «European» norms in the legislation of Ukraine are shown. This «adaptation» discredits the European choice of Ukraine and the adaptation of Ukrainian legislation to the EU acquis communautaire. The violent blow to the rights of property owners was the introduction of the right to arrest property not only of the suspect, the accused, the convict, but also of any third persons, which led to a catastrophic burst of property seizure in the Criminal Procedure Code of Ukraine. As noted on 24.10.2017, the Prime Minister of Ukraine V.B. Groisman, «in Ukraine searches and arrests of property of entrepreneurs became cholera». At the same time, when making such amendments, the explanatory note to the law indicated that it was adopted in order to implement the EU Directive of 03.04.2014 2014/42/ EU on the seizure and confiscation of objects of criminal activity and its proceeds from the EU and the Decision of the Council of the EU 2007/845/JHA of 06.12.2007 on cooperation between returning agencies in the field of tracing and detecting proceeds of crime. Observations show that most of these arrests subsequently prove to be unjustified, but harm people. On October 14, 2014, the Law «On Prevention and Counteraction of the Legalization (Laundering) of the Proceeds from Crime, Terrorist Financing and the Financing of the Proliferation of Weapons of Mass Destruction» was adopted. The explanatory note to the draft law states that the purpose of the draft law is to implement the SBA Agreement with the International Monetary Fund and to take into account proposals for national legislation by FATF experts, the IMF and the Council of Europe for assessing counter measures Money Laundering and Terrorist Financing (MONEYVAL). However, in essence, this law is aimed at increasing the level of pressure on business entities, which even adherents of this law acknowledged. The current practice of restricting the rights of citizens under the slogan of Europeanization, examples of which are set out in the article, discredit the European choice of Ukraine and adaptation of Ukrainian legislation to EU legal norms, creates the basis for changing electoral sentiment in favor of the revenge of anti-European forces in Ukraine.